AB0610 PERSISTENT INFLAMMATION DESPITE TOCILIZUMAB TREATMENT IN 2 PATIENTS WITH LARGE VESSEL VASCULITIS AND AORTIC INVOLVEMENT REQUIRING AORTIC VALVE REPLACEMENT. (June 2019) - Rubbert-Roth, Andrea; Langenegger, Thomas; Bode, Peter Karl; Pfofe, Claudia; Kim, Olaf Chan-Hi; Kempis, Johannes von
Abstract : Background: Tocilizumab (TCZ) has recently been approved for treatment of giant cell arteritis (GCA). Despite clinical, radiologic and serologic improvement in the majority of patients, it remains unclear whether inflammation of the vascular wall in patients with large vessel vasculitis may persist. Objectives: To report 2 patients who were treated with TCZ for large vessel vasculitis involving the ascending aorta. The patients underwent aortic valve replacement in both cases and partial replacement of the ascending aortic arch in one case. Methods: Following therapy with glucocorticosteroids (GC) and TCZ, replacement of the aortic valve and of the partial ascending aorta were performed, followed by a histopathologic examination of the surgical specimen. Results: We report two female patients, aged 40 and 67 years, both diagnosed with large vessel vasculitis involving the aortic arch. Aortitis of the ascending aorta and significant aortic insufficiency were demonstrated in both patients by PET-CT, MR angiography and transesophageal cardiac ultrasound. In Pat 1, PET CT and MR angiography revealed vascular inflammation. Intravenous pulse GC was initiated, followed by oral prednisone with stepwise tapering and TCZ iv 8mg/kg/month. Two weeks after the 2nd infusion of TCZ, MR angiography showed significant reduction of gadolinium enhancement in the wall of the ascending aorta and the patient subsequently underwent valve replacement. Pat 2 was diagnosed with vasculitis of the aortic arch by MR angiography. Therapy with oral GC (1mg prednisone/kg) and methotrexate was initiated. After 12 months, the treatment was switched to TCZ 162mg sc once weekly because of inadequate control of disease. The patient was monitored clinically and by PET CT and GCA was considered well controlled over 4 years. Due to continuous enlargement of the ascending aorta resulting in significant aortic insufficiency, the patient underwent replacement of the aortic valve and the ascending aorta. Both patients showed normalization of CRP and ESR during TCZ treatment. In summary, despite PET-CT and MR angiography showing reduction in vascular wall inflammation before surgery and CRP and ESR normalized, both patients showed histologically persistent lymphoplasmacellular infiltrates (predominantly CD3+CD4+ T cells in patient 1) and, in addition, giant cells in pat 2. Conclusion: Despite adequate control of large vessel vasculitis involving the ascending aorta clinically as well as by imaging, the 2 patients reported here had to undergo valve replacement which showed persistent inflammation of the aortic wall despite treatment with TCZ. Disclosure of interests: Andrea Rubbert-Roth Consultant for: Chugai, Eli Lilly, Roche, and Sanofi, Speakers bureau: abbVie, Bristol-Myers Squibb, Chugai, Hexal/Novartis, Janssen, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, and Sanofi, Thomas Langenegger: None declared, Peter Karl Bode: None declared, Claudia Pfofe: None declared, Olaf Chan-Hi Kim: None declared, Johannes von Kempis: None declared